Carcinogenic Risk of Arsenic (As) in Groundwater and Bottled Water Samples in Covenant University and Canaanland, Ota, Ogun State, Nigeria (Journal of Informatics and Mathematical Sciences, 2017)
This study was conducted in order to estimate the carcinogenic risk of heavy metals exposure via the consumption of groundwater and bottled water for the population of Covenant University and Canaanland, Ota, Ogun state using Perkin Elmer Optima 8000 ICP-OES. The chronic daily intake (CDI) in all the samples ranged from 0.005 and and 0.014\(μ\)gL\({}^{-1}\)kg\({}^{-1}\)d\({}^{-1 }\) which was found to be negligible of potential risk on the inhabitants of different age groups. The carcinogenic Risk (R) for all the samples ranged between 0.01 and 0.025 \(μ\)gL\({}^{-1}\)d\({}^{-1}\). The R for all the age groups was found to be less than the acceptable level of EPA. The highest carcinogenic risk in Arsenic was found in children, which could be attributed to their lower body weight. However, all the values measured were observed to be below the recommended level by USEPA and WHO respectively.
Keywords: Canaanland; Carciniogenic; Covenant; Optima; USEPA; Perkin